Droplets tracing in a T-junction microchannel - Nur Tantiyani Ali Othman; An-Najmi Mohd Farid (Penerbit Universiti Kebangsaan Malaysia, 2018)
Emulsions consist of small liquid droplets immersed in another liquid, typically either a mix of oil in water or water in oil. Emulsions have wide applications in the production of pharmaceutical products, food and cosmetics. The properties and quality of an emulsion typically depend on the size and the distribution of the droplets. Thus, the objective of this study was to investigate in detail the formation and behaviour of droplets in a T-junction microchannel. By setting up a model and applying a laminar two-phase flow in ANSYS© simulation, the particle droplets distribution was observed. The model used the predefined wetted wall boundary condition at the solid walls, with a contact angle of 135°. In this study, the behaviour and flow pattern of the particles along the T-junction microchannel were observed with regard to the effect of the initial particle concentration, the flow rate of the particles, and the initial velocity feed through the inlets of the microchannel. From the results, the effects of the velocity, mixing time and flow rate of the particles on the particle distribution and mixing were studied. It was shown that the optimization process was achieved at a flow rate of 0.025 mL/s, with the mixing process occurring within 1.6 seconds and the velocity feed at the two inlets being VA = 0.02 m/s and VB = 0.04 m/s, where the particles experienced less lift shear and compressive forces near the outlet, which caused the mixing process to become efficient.